Factors that Influence Foreign Students Decision to Enrol into Tertiary Private Education in Private Universities in Nilai, Negeri Sembilan, Malaysia - Ahmed, Mohsin (2016)
Malaysian education industry has been growing aggressively along with the aspiration of being a regional education hub by achieving the goal of gaining 200, 000 international students to pursue their education in Malaysia by 2020. However, there is little knowledge regarding to international student’s university choice in terms of continue pursuing study in private higher education institutions in Nilai Malaysia. This research focuses on three independent variables which are Effort Expectancy, Facilitating Condition, Social Influence institutional information and people (lecturers, peers and friends) and it aims to determine what are the factors influence international student’s intention to continue pursuing study in Nilai, Malaysia. A total of 200 international undergraduates from different countries who are currently studying in Nilai, Malaysia were selected by using convenient sampling method to answer the structured and self-administrated online questionnaires. The collected data was analysed using normality test, reliability test, validity test and multiple regression by Statistical Package for the Social Sciences –SPSS. Results indicate factors that influence foreign student’s decision to enrol into tertiary private education in private universities in Nilai, Negeri Sembilan, Malaysia. Although the rest of the three independent variables failed to established significant relationships with the dependent variable, facilities and social influence and effort expectancy were highly ranked by the respondents as Important factors as well; whereas the other variables were ranked as the least important factors to their intention of continue pursuing studies in Nilai, Malaysia.